Structural, vibrational, and electronic properties of BaReH9 under pressure. (28th October 2016) - Vinitsky, Eugene A; Muramatsu, Takaki; Somayazulu, Maddury; Wanene, Wilson K; Liu, Zhenxian; Chandra, Dhanesh; Hemley, Russell J
Abstract: We present a study of the high-pressure behavior of BaReH9, a novel hydrogen-rich compound, using optical, Raman, and infrared spectroscopy as well as synchrotron x-ray diffraction. The x-ray diffraction measurements demonstrate that BaReH9 retains its hexagonal structure on room temperature compression up to 40 GPa. Optical absorption shows the absence of a gap closure to 80 GPa. Raman and IR spectra reveal the pressure evolution of a newly observed phonon peak, and large peak broadening with increasing pressure. These data constrain the disorder present in the material following the P - T paths explored.